Application of the Concept of Butterfly Edu-Ecotourism as a Manifestation of Real Work Lecture Activities at the Kerandangan Nature Tourism Park: Penerapan Konsep Edu-Ekowisata Kupu-kupu Sebagai Perwujudan Kegiatan Kuliah Kerja Nyata di Taman Wisata Alam Kerandangan - Reginah Fhathonah Insani; Habibah Habibah; Intan Putri Yasa; Lalu Ahmad Azfani; Masnayati Hilmi; Maulidatin Nanisfi; Norma Azizah; Rita Alawiyah; Siti Diniah; Vines Salsa Imami (Yayasan Siti Widhatul Faeha, 2025)
The Real Work Lecture (KKN) in the 2023 Independent Study activity was held at the Kerandangan Nature Tourism Park, Keranganangan Hamlet, Senggigi Village, Batu Layar District, West Lombok Regency. This activity carries the theme